Assessment of out-of-field doses in radiotherapy treatments of paediatric patients using Monte Carlo methods and measurements. (March 2020) - Cravo Sá, Ana; Barateiro, Andreia; Bednarz, Bryan; Borges, Cecília; Pereira, Joana; Baptista, Mariana; Pereira, Miguel; Zarza-Moreno, Miriam; Almeida, Pedro; Vaz, Pedro; Madaleno, Tiago; Romanets, Yuriy
Highlights: Out-of-field doses in radiotherapy treatments of paediatric patients. Dosimetric measurements in radiotherapy clinical settings. Voxelization of a physical paediatric phantom. MCNP6 model of a linear accelerator. Validation of MC model through comparison with clinical measurements. Abstract: Purpose: To assess out-of-field doses in radiotherapy treatments of paediatric patients, using Monte Carlo methods to implement a new model of the linear accelerator validated against measurements and developing a voxelized anthropomorphic paediatric phantom. Methods: CT images of a physical anthropomorphic paediatric phantom were acquired and a dosimetric planning using a TPS was obtained. The CT images were used to perform the voxelization of the physical phantom using the ImageJ software and later implemented in MCNP. In order to validate the Monte Carlo model, dose measurements of the 6 MV beam and Linac with 120 MLC were made in a clinical setting, using ionization chambers and a water phantom. Afterwards TLD measurements in the physical anthropomorphic phantom were performed in order to assess the out-of-field doses in the eyes, thyroid, c-spine, heart and lungs. Results: The Monte Carlo model was validated for in-field and out-of-field doses with average relative differences below 3%. The average relative differences between TLD measurements and Monte Carlo is 14, 3% whilst the average relative differences between TLD and TPS is 55, 8%. Moreover, organs up to 22.5 cm from PTV center show TLD and MCNP6 relative differences and TLD and TPS relative differences up to 21.2% and 92.0%, respectively. Conclusions: Our study provides a novel model that could be used in clinical research, namely in dose evaluation outside the treatment fields. This is particularly relevant, especially in pediatric patients, for studying new radiotherapy treatment techniques, since it can be used to estimate the development of secondary tumours.